PENGARUH KINERJA KEUANGAN TERHADAP KEMAMPUAN PENYALURAN KREDIT PADA BANK UMUM SWASTA NASIONAL DEVISA GO PUBLIC - Jazilatun Najakhah; Saryadi Saryadi; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2014)
Bank as financial institution that serves as financial intermediary, necessary grades of healthy for know bank condition. Health or not a bank can see from bank financial performance. The ratio of financial analysis the content in financial performance a bank beneficial to do a prediction agains the provision of credits the future. With a good performance, the bank can do one of the main function is to give and distribute the credit to debitor. The troubles in this research is the presence of dissent from the result of further researches first and the phenomenon of bank lending has not been optimal. The research aims to find the empirical facts of the influence of financial performance with CAEL method to credit loan.The research belongs to “explanatory research”. Analytical method used in this research is a simple regression test to the test partially the significance test using t test and regression test to simultaneously test for the significance test using the F test. Object in this research is a national private commercial banks foreign exchange 2010-2012. Number of samples used were 21 bank in the sample.Result and discussion indicate from partial test show the CAR and NPL variables have negative influence and significance to the credit distribution. ROE variable has positive influence and significance to the credit distribution. For ROA and LDR variables does not influence to the credit distribution. While based on the results of simultaneous hypothesis tests (F test) showen that the CAR, NPL, ROA, ROE and LDR has a significant influence on the credit distribution. The result of coefficient determinated is 0,337. This suggests that the major influence of the independent variable is CAR, NPL, ROA, ROE and LDR of the dependent variable (credit distribution) of 33,7%, while the remaining 66,3% can be explained by other variables outside this model.Suggestion that can be conveyed based on the result analysis indicated that the management of the bank necessary attention to CAR and NPL. Because both the ratio of the bank financial is variable the most dominan in effecting a decrease in credit distribution. It is a need to study further about factor influence to credit distribution, from internal or external factors a bank.